(untitled) (Journal of the College of Basic Education, 2024)
The current research aims to identify the level of triple intelligence among students - teachers in the mathematics departments in the colleges of basic education. The basic course, in its final form, consisted of (27) items of multiple choice type, and essay tests divided into (3) abilities, analytical ability (10) items, creative ability (10) items, practical ability (7) items, and the validity was verified and stability of the tool. After the tool became ready for application, the test was applied to the research sample, and statistical treatments were performed using the appropriate statistical means based on the statistical package Spss. The level of male and female students’ possession of the triple intelligence was close, as the values ​​of the arithmetic averages were close, then a number of recommendations and proposals were made.